Thomas Aquinas and his criticism of Avempace's theory of the intellect - Matula, Jozef (Verbum – Analecta Neolatina, 2004)
The article deals with Aquinas' relation to Avempace's theory of intellect, especially with his criticism of the conception of agent intellect as presented by Avempace. The author examines the parts of Aquinas' works where he rejects Avempace's theory of coniunctio as a union with the divine realm and Avempace's identification of imagination with intellect. The criticism is founded on the background of Aquinas' discussion with Averroism. The second part of the article deals with Aquinas' criticism of Avempace's theory of speculative sciences, which consist of he problem whether the ultimate happiness of man is to understand the separate substances. Aquinas criticizes the theory according to which through the pursuit of the speculative sciences man comes to the understanding of separate substances from the sensible things. Aquinas is very sceptical of this opinion and he strictly follows Aristotle's emphasis on senses and phantasms. The only things a human being can know in the speculative sciences are those that are grounded within the range of naturally known principles. The author shows the metaphysical presuppositions of Aquinas and Avempace which are momentous for the understanding of the diVerent interpretations of Aristotle.